Konsekuensi Ekonomik dari Regulasi Akuntansi Goodwill: Pengalaman Australia - Nurkholis Nurkholis (The Indonesian Journal of Accounting Research, 2013)
This study focuses on revealing the economic consequences of goodwill accounting regulation in Australia.  It attempts to achieve three main purposes: (1) to reveal the relationship between bonus compensation plans and managers’ agreement/disagreement with Australian goodwill accounting standard, AASB 1013, (2) to examine the relationship between acquisition made by companies and managers’ agreement/disagreement with the accounting standard, and (3) to test whether there is a significant difference between managers’ and public accountants’ agreement/ disagreement with the standard. Data of this research were gathered through mail survey. Respondents participated include 80 accounting managers of publicly listed companies and 70 public accountants which, altogether, represent 50% response rate. The quantitative approach (independent sample t-test and ANOVA) is used to address the research questions. This study reveals that the goodwill accounting regulation in Australia has had economic consequences which have been evident by the finding that managers with bonus compensation plan showed greater disagreement (compared with managers without bonus compensation plan) in the duration of twenty years allowed to amortize goodwill. This is supported by further evidence that managers have shown significantly stronger disagreement with the goodwill standard compared to public accountants which were less likely to be affected by the goodwill accounting regulation.